Development of Learning Media for Tutors Based on Video Tutorials on the "Setara Daring" Application at PKBM in the Medan City Area - Keysar Panjaitan; Ederlina M. Acedo; Shahid Hussain (Classroom Experiences, 2025)
SeTARA Daring provides a range of facilities that enable online teaching and learning, including convenient access for tutors and learners via various digital devices. This study aimed to develop and describe the procedure for producing video-tutorial–based learning media for use in the “SeTARA Online” application by tutors at PKBM East Medan, and to evaluate the effectiveness of the resulting media. The research object was a KineMaster-based video tutorial designed to support tutors in creating effective instructional media within the SeTARA Daring platform. Data were collected using a questionnaire, and were analyzed using Aiken’s V to establish content validity, complemented by a t-test and normalized gain (N-gain) analysis to examine learning improvements. The findings indicate that the developed video tutorial achieved very high validity, with Aiken’s V approaching 1.00, suggesting that the content and presentation were highly appropriate and aligned with the instructional material. In addition, the video-based media not only supported students’ understanding of the learning content but also encouraged tutors to adopt more creative and innovative instructional practices. Results from the pretest–posttest analysis further demonstrated a statistically significant improvement in student learning outcomes among those who learned with the KineMaster-based video media compared with those who did not. Overall, the study concludes that KineMaster-based video tutorials are feasible and effective for supporting learning through the SeTARA Daring application. Future research is recommended to extend implementation to broader contexts and to further examine impacts on learning outcomes across different learner groups.